Une chambre à soi : genres et corps en art - Luc Schicharin; Anne-Laure Vernet (Glad!)
During the course of 2 symposium respectively called « Genderqueer Workshop : a Reflexion on Contemporary Bodies through the Arts », and « A Room to One’s Own : Genders and Bodies in Art » held from March 2015 to January 2016, the problematic of political subjectivity has been approached through an aestethical and philosophical study of works of art which are organized according to the codes of contemporary art and of militant artistic practices coming from subcultures and popular cultures. Thanks to the interdisciplinarity of the many lecturers, all coming from an international network, the diversity in epistemological analytic context, methodology and analysis, allowed an approach both sharp and renewed of the problematic of the contemporary bodies in art. The filming of the symposiums and of the conversations and debates that they provoqued led to the making of several short movies. The aim is to use them as shortened and summarized version of those scientific discussions, but also as the start of an ethnographic study of this scientific process, and as an innovative way of sharing this scientific coelaboration through digital support.